Mosquitoes of Kudat: species composition and their medical importance(diptera: culicidae) - Ng, S.H.; Homathevi R.,; Chua, T.H. (Pusat Sistematik Serangga, Fakulti Sains dan Teknologi, Universiti Kebangsaan Malaysia, 2016)
A survey of mosquito fauna was done to determine the mosquito population and species composition in Kudat. Outdoor human landing catches (HLC) were done from April to June 2015. A total of 4,350 mosquitoes, representing eight genera and 37 species were collected. These include Aedes (Stegomyia), Aedimorphus, Anopheles, Armigeres, Culex, Mansonia, Phagomyia and Uranotaenia. Medical important species are specially noted and discussed. Armigeres (52.7%) was the most abundant, followed by Culex (31.9%), Aedes (9.4%), and Anopheles (4.3%). Armigeres kesseli and Ar. subabaltus were the two most common species. Armigeres annulipalpi and Phagomyia prominens are new records of Sabah.